RETRACTED: Agrotourism in the development of the agricultural economy of the Republic of Uzbekistan and its foreign experience - Askarova Mavluda; Khafizova Zulfiya; Talipova Dilfuza; Yakubov Iskandar; Khayitov Saidjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001